Behaviour of silver nanoparticles and silver ions in an in vitro human gastrointestinal digestion model. Issue 7 (November 2012) - Walczak, Agata P.; Fokkink, Remco; Peters, Ruud; Tromp, Peter; Herrera Rivera, Zahira E.; Rietjens, Ivonne M.C.M.; Hendriksen, Peter J.M.; Bouwmeester, Hans
Abstract Oral ingestion is an important exposure route for silver nanoparticles (AgNPs), but their fate during gastrointestinal digestion is unknown. This was studied for 60 nm AgNPs and silver ions (AgNO3) using in vitro human digestion model. Samples after saliva, gastric and intestinal digestion were analysed with SP-ICPMS, DLS and SEM-EDX. In presence of proteins, after gastric digestion the number of particles dropped significantly, to rise back to original values after the intestinal digestion. SEM-EDX revealed that reduction in number of particles was caused by their clustering. These clusters were composed of AgNPs and chlorine. During intestinal digestion, these clusters disintegrated back into single 60 nm AgNPs. The authors conclude that these AgNPs under physiological conditions can reach the intestinal wall in their initial size and composition. Importantly, intestinal digestion of AgNO3 in presence of proteins resulted in particle formation. These nanoparticles (of 20–30 nm) were composed of silver, sulphur and chlorine.